2020
DOI: 10.2147/ott.s240642
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA 0060745, a Novel circRNA, Promotes Colorectal Cancer Cell Proliferation and Metastasis Through miR-4736 Sponging</p>

Abstract: Purpose: Recent studies have shown that noncoding RNAs (ncRNAs) play essential roles in the development of a number of cancers. Circular RNAs (circRNAs) have been shown to contribute to the progression of colorectal cancer (CRC). Methods: In this study, the expression levels of circular RNA 0060745 (circ_0060745), and microRNA 4736 (miR-4736) were measured using qRT-PCR. Kaplan-Meier survival analysis and receiver operating characteristic (ROC) analysis were used to evaluate the diagnostic value of circ_006074… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Also, different circRNAs have been implicated in the developing process of CRC. The previous studies have affirmed some oncogenic factors (circ_0060745, circHIPK3) and tumour suppressors (circ_0002138, circDDX17) in CRC 32‐35 . The expression analysis for circ_0007142 in this study indicated that it was abnormally upregulated in CRC samples and cells.…”
Section: Discussionsupporting
confidence: 62%
“…Also, different circRNAs have been implicated in the developing process of CRC. The previous studies have affirmed some oncogenic factors (circ_0060745, circHIPK3) and tumour suppressors (circ_0002138, circDDX17) in CRC 32‐35 . The expression analysis for circ_0007142 in this study indicated that it was abnormally upregulated in CRC samples and cells.…”
Section: Discussionsupporting
confidence: 62%
“…Ren et al revealed that hsa_circ_0001178 functions as a ceRNA for miR-382/587/616 to upregulate ZEB1 (a key trigger of EMT), subsequently facilitating the metastatic dissemination of CRC [ 119 ]. In addition, specific circRNAs promote the transcription of their host genes [ 89 ] or protect their homologous mRNAs from miRNA-mediated degradation by inhibiting miRNA activity [ 105 , 133 ]. For example, Wang et al revealed that hsa_circ_0060745, a circRNA derived from exons 9 and 10 of CSE1L, functions as a ceRNA to sequester miR-4736 and promotes the CSE1L-mediated proliferation and metastasis of CRC cells [ 133 ].…”
Section: Circrnas and Crcmentioning
confidence: 99%
“…In addition, specific circRNAs promote the transcription of their host genes [ 89 ] or protect their homologous mRNAs from miRNA-mediated degradation by inhibiting miRNA activity [ 105 , 133 ]. For example, Wang et al revealed that hsa_circ_0060745, a circRNA derived from exons 9 and 10 of CSE1L, functions as a ceRNA to sequester miR-4736 and promotes the CSE1L-mediated proliferation and metastasis of CRC cells [ 133 ]. Lai et al concluded that hsa_circ_0079662 (circHOXA9), a ceRNA that binds hsa-mir-324-5p, upregulates the expression of the target gene HOXA9 and induces oxaliplatin resistance in human colon cancer through the TNF-α pathway [ 105 ].…”
Section: Circrnas and Crcmentioning
confidence: 99%
“…CircRNAs are transcripts that are closed covalently and are resistant to exoribonuclease degradation, which are usually more stable than linear transcripts [5]. Aberrant circRNA expression has been discovered in many kinds of cancers such as breast [6], colorectal [7], gastric [8], and lung [9]. For prostate cancer, studies show that circLMTK2 acts as tumor suppressor in PCa through regulating microRNA-183 expression [10].…”
Section: Introductionmentioning
confidence: 99%